Social Capital Trends in Germany in the Face of the Covid-19 Pandemic: A Research Note - Burrmann, Ulrike; Mutz, Michael; Sielschott, Stephan; Braun, Sebastian (Frontiers in Political Science, 2022)
This research note reports social capital trends in Germany during the COVID-19 pandemic. It is based on a comparison of survey data from 2017/18 and 2020/21, i.e., trends reported here inform about changes of social capital levels during the “second lockdown” of the pandemic, when containment policies were in effect throughout the country. Findings point to stable levels of in-group trust, out-group trust and prosocial attitudes. At the same time, sociability orientations are lower and society is generally perceived as less solidary. Members in voluntary organizations have more social capital compared to non-members—this difference is found before as well as during the pandemic. Regarding that changes are generally small, it can be concluded that the pandemic did neither strengthen social capital considerably, nor did it lead to a massive overall decline of social capital.